Akulturasi Islam Pada Budaya Kenduri Ketupat Pada Bulan Ramadhan - Ismail Effendi Nasution; Resha Khofila; Mhd. Ulul Azmi; Muhammad Syukri Albani Nasution; Imam El Islamy (Fakultas Dakwah dan Komunikasi UIN Sumatera Utara Medan, 2023)
The purpose of this study is to provide light on cultural acculturation in the Ramadan-related Kenduri Ketupat tradition in Hamlet III, Bedimbar Tanjung Morawa Village. To do this, researchers employ research techniques that take a religious anthropological stance in an effort to comprehend the true significance of the studied object. The analysis in this study adopts a phenomenological or qualitative method that is descriptive in character. The results of this study suggest that cultural acculturation in Kenduri Ketupat in Buntu Bedimbar Village, Tanjung Morawa, which is carried out every mid-Ramadan month, is the identity of the Muslim community in social-religious activities. The philosophy of cultural acculturation in Kenduri Belah Ketupat is that the month of Ramadan can continue to be sticky and dense so that the worship that is done can continue to stick in the heart as sticky rice cake in a diamond. Pulut, which is attached to the diamond, means that the worship in the month of Ramadan can remain sticky and dense